Increasing compliance with mass drug administration programs for lymphatic filariasis in India through education and lymphedema management programs. - Paul T Cantey; Jonathan Rout; Grace Rao; John Williamson; LeAnne M Fox (Public Library of Science (PLoS), 2010)
Nearly 45% of people living at risk for lymphatic filariasis (LF) worldwide live in India. India has faced challenges obtaining the needed levels of compliance with its mass drug administration (MDA) program to interrupt LF transmission, which utilizes diethylcarbamazine (DEC) or DEC plus albendazole. Previously identified predictors of and barriers to compliance with the MDA program were used to refine a pre-MDA educational campaign. The objectives of this study were to assess the impact of these refinements and of a lymphedema morbidity management program on MDA compliance.A randomized, 30-cluster survey was performed in each of 3 areas: the community-based pre-MDA education plus community-based lymphedema management education (Com-MDA+LM) area, the community-based pre-MDA education (Com-MDA) area, and the Indian standard pre-MDA education (MDA-only) area. Compliance with the MDA program was 90.2% in Com-MDA+LM, 75.0% in Com-MDA, and 52.9% in the MDA-only areas (p<0.0001). Identified barriers to adherence included: 1) fear of side effects and 2) lack of recognition of one's personal benefit from adherence. Multivariable predictors of adherence amenable to educational intervention were: 1) knowing about the MDA in advance of its occurrence, 2) knowing everyone is at risk for LF, 3) knowing that the MDA was for LF, and 4) knowing at least one component of the lymphedema management techniques taught in the lymphedema management program.This study confirmed previously identified predictors of and barriers to compliance with India's MDA program for LF. More importantly, it showed that targeting these predictors and barriers in a timely and clear pre-MDA educational campaign can increase compliance with MDA programs, and it demonstrated, for the first time, that lymphedema management programs may also increase compliance with MDA programs.